Rejecting the myth of equal opportunity: an agenda to eliminate racism in nursing education in the United States - Kechinyere C. Iheduru-Anderson; Monika M. Wahi (BMC, 2021)
Abstract Background Unfortunately, racism and discrimination against Ethnic minority (EM) has been globalized, universally infecting industries worldwide, and the field of nursing has not been spared. In the United States (US), overt and institutionalized racism (IR) still permeates the fields of nursing, nursing leadership, and nursing education. Programs to address these disparities, and efforts by nursing professional societies and nursing education policymaking bodies to address racism in the nursing field, specifically with nursing leadership and education, have met with little success. Objective The purpose of this paper is to illustrate the existence and magnitude of racism and its impact on the fields of nursing, nursing leadership, and nursing education, and to make evidence-based recommendations for an agenda for reforming nursing education in the US. Methods A narrative literature review was conducted with a focus on pulling together the strongest evidence on which to base policy recommendations. Results Based on the available literature, we put forth five recommendations aimed at modifying nursing education in the US as a strategy to counter IR in the US in the nursing field. Conclusions Recommendations to address IR in nursing focus on nursing education, and involve implementing programs to address the lack of opportunity for both EM students and faculty in nursing, developing an anti-discriminatory pedagogy, and incorporating diversity initiatives as key performance indicators (KPIs) in the process of approval and accreditation of nursing programs.